Access to the Unified Health System in the perspective of male homosexuals - Luís Eduardo Soares dos Santos; Wemerson dos Santos Fontes; Ana Karla Sousa de Oliveira; Luisa Helena de Oliveira Lima; Ana Roberta Vilarouca da Silva; Ana Larissa Gomes Machado
ABSTRACT Objectives: To analyze the perception of male homosexuals regarding the access to the Unified Health System. Methods: A qualitative study with male homosexuals in a city in the Northeast Brazil. Eight subjects participated, a socioeconomic questionnaire was used for data collection and a focal group was carried out, in which the narratives were recorded and later transcribed. For the analysis of the speeches, the analysis of thematic content was used. Results: The analysis revealed five thematic categories that express the limitations on humanization and reception, as well as in the quality of health care offered to subjects, disregarding the psychosocial and lifestyle-related demands. Final considerations: It was emphasized that the focus group technique contributed to the approach of the research with the perception of male homosexuals marked by prejudice and discrimination, reflecting the subjects' dissatisfaction with the care received in the health services.